2023
DOI: 10.1039/d2nr07091j
|View full text |Cite
|
Sign up to set email alerts
|

Improving anion-exchange efficiency and spectrum stability of perovskite quantum dots via an Al3+ bonding-doping synergistic effect

Abstract: Anion-exchange reactions have been recognized as a vital and facile post-synthetic method to precisely manipulate the emission spectra of perovskite quantum dots (QDs). However, the anion-exchange process often induces adverse...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…[6][7][8][9][10] Generally, blue emission can be achieved by modulating the quasi-two-dimensional (quasi-2D) quantum well distribution, enhancing the quantum confinement effect of CsPbBr 3 , or doping Cl species to change the degree of orbital overlap, respectively. [11][12][13][14][15][16][17][18][19][20] In recent years, there has been a significant focus on developing blue PeLEDs based on the first two techniques. However, it is reported that low-dimensional perovskites exhibit inefficient energy transfer, spectral broadening and even multi-peak emission owing to their complicated phase distribution.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Generally, blue emission can be achieved by modulating the quasi-two-dimensional (quasi-2D) quantum well distribution, enhancing the quantum confinement effect of CsPbBr 3 , or doping Cl species to change the degree of orbital overlap, respectively. [11][12][13][14][15][16][17][18][19][20] In recent years, there has been a significant focus on developing blue PeLEDs based on the first two techniques. However, it is reported that low-dimensional perovskites exhibit inefficient energy transfer, spectral broadening and even multi-peak emission owing to their complicated phase distribution.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, trioctyl phosphine oxide (TOP), aluminum( iii ) acetylacetonate (Al(acac) 3 ), and polymethyl methacrylate (PMMA) have been used to passivate mixed halide perovskite NCs to reduce the defect density and inhibit phase separation. 26–28 Nevertheless, the overall stability of these mixed perovskite NCs shows a limited improvement under the synergistic effects of light and heat, which are usually the case in LED backlights. Thus, balancing the stability and optical properties of mixed halide perovskite NCs is the key to their practical display applications.…”
Section: Introductionmentioning
confidence: 99%